Shaft sleeve bearing bush special for aluminum-silicon wire as well as preparation method and application of shaft sleeve bearing bush

By covering the base material of the aluminum-silicon wire bushing bush with CoCrAlY/Y2O3-Si/SiC and CoCrAlY-YSZ composite coatings, combined with silicone-based resin coating, the problem of poor wear resistance and corrosion resistance of the bushing bush is solved. The long-term effectiveness and stability of the bushing and bearing are achieved.

CN119332190AActive Publication Date: 2025-01-21ANHUI MA STEEL SURFACE TECH CO LTD

Patent Information

Application Number
CN202411902223.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The bearing bushings of aluminum-silicon spools have poor wear resistance and corrosion resistance, and their lifespan is very short. The actual service life is extremely unstable. Some bearing bushings fail after less than one day they are on the line.

Method used

Cobalt-based heat-resistant alloy or 316L stainless steel is used as the base material of the bushing and bushing, covered with composite coatings, including CoCrAlY/Y2O3-Si/SiC and CoCrAlY-YSZ coatings, deposited by supersonic flame spraying or laser cladding technology, combined with Silicone resin coating improves heat and corrosion resistance.

Benefits of technology

It significantly improves the wear -resistant and corrosion resistance of the axis tile, extends the service life, ensures the stability of the actual service life, and avoids the crushing and wear of the bearing tile.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332190A_ABST
    Figure CN119332190A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surfaces, in particular to a special shaft sleeve and bearing bush for an aluminum-silicon wire, a preparation method and application of the special shaft sleeve and bearing bush for the aluminum-silicon wire, a composite coating covers a grinding part on a base material of the shaft sleeve and bearing bush, other parts are coated with silicon-based resin, and the base material of the shaft sleeve and bearing bush is cobalt-based heat-resistant alloy or 316L stainless steel. The material system of the composite coating at the opposite-grinding part of the shaft sleeve is CoCrAlY / Y2O3-Si / SiC, the thickness of the coating is 0.4-1.0 mm, the material system of the composite coating at the opposite-grinding part of the bearing bush is CoCrAlY-YSZ, and the thickness of the coating is 0.5-1.5 mm. The high-temperature-resistant, corrosion-resistant, wear-resistant and fragmentation-resistant shaft sleeve bearing bush suitable for the aluminum-silicon wire has good lubricity at a high temperature, and the service life of the shaft sleeve bearing bush is prolonged. Abrasion of the shaft sleeve bearing bush can be greatly reduced, fragmentation of the bearing bush is avoided, the service life of the shaft sleeve bearing bush is further prolonged, and it is guaranteed that the actual service life of the shaft sleeve bearing bush is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface technology, and in particular to a shaft sleeve and bearing shell special for aluminum silicon wire, a preparation method and application thereof. Background Art

[0002] Hot-dip aluminum silicon (AlSi) coatings are mainly used for applications that require formability, high temperature resistance, and heat reflection, such as automobile exhaust pipes, mufflers, engine heat shields, various heat exchangers, and photovoltaic solar cell substrates.

[0003] In the hot-dip AlSi coating production line (AlSi line for short), the AlSi pot is the part with the worst service conditions among the process equipment in the entire production line. This is because the temperature inside the aluminum-silicon plating pot (about 650-700℃) is high, and aluminum is more active than zinc. In the high-temperature molten state, it has a stronger corrosive effect on roller components immersed in the pot. The service life of the sleeves and bearings in the pot is only 2-4 days under the corrosion of high-temperature liquid molten aluminum-silicon. The production line cannot increase production and efficiency due to the need to frequently replace sleeves and bearings.

[0004] At present, the friction pairs of aluminum-silicon wire shaft sleeves and bearings can be divided into two categories according to the material: 1. Alloy sleeves with alloy bearings, which have poor wear and corrosion resistance and a very short service life; 2. Thermal spraying / laser cladding coating sleeves with ceramic bearings (typical structures such as Chinese invention patent application CN202111540512.3), which have relatively good wear and corrosion resistance and can serve for up to about 7 days. The main problem is that there is a large mismatch in thermal expansion coefficients between ceramic bearings and alloy bushings, which can easily cause shaking and ceramic bearing breakage during service (whether it is O-type, two-point or three-point, such problems exist), resulting in the actual service life of bearings and sleeves being extremely unstable, and some bearings and sleeves fail within less than 1 day of being online.

[0005] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0006] The purpose of the present invention is to solve the problems that the current aluminum-silicon wire shaft sleeve and bearing have poor wear resistance and corrosion resistance, very short service life, extremely unstable actual service life, and some bearing sleeves and bushes fail within less than 1 day of being put into operation. A special shaft sleeve and bearing for aluminum-silicon wire, a preparation method and application thereof are provided.

[0007] In order to achieve the above-mentioned purpose, the present invention discloses a special shaft sleeve and bearing for aluminum-silicon wire, wherein the grinding parts on the shaft sleeve and bearing base material are covered with a composite coating, and other parts are coated with a silicon-based resin, the base material of the shaft sleeve and bearing is a cobalt-based heat-resistant alloy or 316L stainless steel, the composite coating material system of the grinding parts of the shaft sleeve is CoCrAlY / Y2O3-Si / SiC, and the coating thickness is 0.4~1.0mm, and the composite coating material system of the grinding parts of the bearing is CoCrAlY-YSZ, and the coating thickness is 0.5~1.5mm.

[0008] Because the temperature in the aluminum silicon wire pot (about 650-700℃) is high, and aluminum is more active than zinc, it has a strong corrosive effect on the sleeve and bearing immersed in the pot in the high-temperature molten state, so the base material of the bearing sleeve should be selected from a heat-resistant and corrosion-resistant alloy; the selection of the sleeve and bearing friction pair is very important, and it is one of the most important factors that determine the service life of the sleeve and bearing, but the selection of the friction pair is quite particular: first, the friction pair cannot react sustainably with molten Al and Si at high temperatures, second, the friction pair must withstand high temperatures of about 700℃ and still have a certain hardness and wear resistance at high temperatures, and third, the wear of the friction pair in the service environment should not be too large. After long-term practical exploration, the inventor found that Si / SiC and YSZ are a pair of friction pairs that meet the above conditions. Because the sleeve and bearing base material is a heat-resistant and corrosion-resistant alloy, if the Si / SiC-YSZ friction pair system is directly deposited on the substrate, it is easy to fail due to CTE mismatch at high temperatures, so a suitable transition layer is required to improve its CTE matching.

[0009] Metal-metal friction pairs and metal / metal ceramic-ceramic friction pairs usually suffer from severe adhesive wear at high temperatures, while ceramic-ceramic systems are more likely to suffer from extremely severe abrasive wear. The present invention adopts semiconductor / ceramic-ceramic friction pairs, which have significantly lighter adhesive wear. Si has good bonding, high-temperature lubricity and toughness, which can avoid the abrasive wear of pure ceramic-ceramic systems. SiC is filled in Si as a hard wear-resistant phase, which improves the wear resistance of Si / SiC. Therefore, Si / SiC and YSZ have relatively good service performance as friction pairs in aluminum silicon wires.

[0010] At present, the ceramic bearings on the market are usually assembled with pure ceramic tiles and metal tile seats at high temperature. However, the temperature of the aluminum silicon wire is significantly higher than that of the zinc pot, and the process operation range of the gap assembly is significantly narrower. Therefore, it is easy to fail prematurely due to "broken tiles" during actual use due to problems such as assembly gap and processing accuracy. The present invention directly uses spraying / laser technology to deposit the above composite coating on the sleeve and bearing, avoiding the above problems and ensuring the consistency of the sleeve and bearing life. According to the material of the covering coating and the requirements for the coating performance, the sleeve and bearing need to be prepared using a suitable process.

[0011] The present invention also discloses a method for preparing the above-mentioned shaft sleeve and bearing shell specially used for aluminum silicon wire, which comprises the following steps:

[0012] S1, using supersonic flame spraying technology or laser cladding technology to deposit CoCrAlY / Y2O3 raw material powder and Si / SiC raw material powder on the sleeve to form a CoCrAlY / Y2O3-Si / SiC coating, and using supersonic flame spraying technology, atmospheric plasma spraying technology or laser cladding technology to deposit a CoCrAlY-YSZ coating on the bearing shell;

[0013] S2, spraying liquid silicon-based polymer precursor onto the shaft sleeve and bearing by brushing or liquid spraying, depositing it onto the position of the shaft sleeve and bearing not covered by the thermal spraying / laser cladding coating, and curing it in a high temperature environment of 200~400℃, so as to obtain heat-resistant and corrosion-resistant silicon-based resin.

[0014] In the step S1, the CoCrAlY / Y2O3 raw material powder is prepared from CoCrAlY and Y2O3 by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of CoCrAlY to Y2O3 is 5:1-50:1.

[0015] In the step S1, the Si / SiC raw material powder is prepared from Si and SiC by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of Si to SiC is 20:1-1:20.

[0016] In the step S1, the CoCrAlY / YSZ raw material powder is prepared by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation of CoCrAlY and YSZ, and the mass ratio of CoCrAlY to YSZ is 5:1-50:1.

[0017] The invention also discloses the application of the above-mentioned shaft sleeve and bearing shell specially used for aluminum-silicon wire in a hot-dip AlSi coating production line.

[0018] The invention also discloses the application of the above-mentioned shaft sleeve and bearing shell dedicated for aluminum silicon wire in a hot-dip galvanizing or zinc alloy production line.

[0019] Compared with the prior art, the beneficial effect of the present invention is that the high temperature resistant, corrosion resistant, wear resistant and crack resistant shaft sleeve and bearing suitable for aluminum silicon wire in the present invention has good lubricity at high temperature, can greatly reduce the wear of the shaft sleeve and bearing, and avoid the cracking of the bearing, thereby further extending the service life of the shaft sleeve and bearing, and ensuring that the actual service life of the shaft sleeve and bearing is relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 (a) is a morphology of the grinding ball after friction and wear between Example 1 and the YSZ grinding ball at room temperature (scale is 500 μm);

[0021] Figure 1(b) is a morphology of the grinding ball after friction and wear between Example 1 and the YSZ grinding ball at room temperature (scale is 200 μm);

[0022] Figure 2 (a) is a morphology of the grinding balls of Comparative Example 1 and YSZ grinding balls after friction and wear at room temperature (scale is 500 μm);

[0023] Figure 2 (b) is a morphology of the grinding balls of Comparative Example 1 and YSZ grinding balls after friction and wear at room temperature (scale is 200 μm);

[0024] Fig. 3 (a) is the morphology of the grinding ball after friction and wear between the grinding ball of Example 1 and Al2O3 at room temperature (scale is 500μm);

[0025] Fig. 3(b) is the morphology of the grinding ball after friction and wear between the grinding ball of Example 1 and Al2O3 at room temperature (scale is 200μm);

[0026] Figure 4 The wear scar data of friction and wear between Example 1 and YSZ grinding ball at room temperature;

[0027] Figure 5 The wear scar data of the friction and wear of the comparative example 1 and the YSZ grinding ball at room temperature;

[0028] Figure 6 The wear scar data of the friction and wear of the grinding ball between Example 1 and Al2O3 at room temperature;

[0029] Figure 7 The comparison results of wear volume, half-height width and wear scar depth between Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] (1) CoCrAlY / Y2O3 and Si / SiC coatings were sprayed on 316L stainless steel specimens in sequence by supersonic flame spraying. The supersonic flame spraying process parameters are shown in Table 1. The coating thickness is 350 μm.

[0033] (2) Grind and polish the plate surface coating used in step (1) to a roughness of <Ra0.4μm。

[0034] Table 1 Process parameters of HVOF CoCrAlY / Y2O3 and Si / SiC coatings

[0035]

[0036] Example 2

[0037] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0038] (2) Process the bearing sleeve blank according to the drawing;

[0039] (3) CoCrAlY / Y2O3 and Si / SiC coatings were sprayed on the sleeve in sequence using supersonic flame spraying technology. The process parameters are shown in Table 1. The total coating thickness is 0.8 mm.

[0040] (4) CoCrAlY and YSZ coatings were sprayed on the bearing shells in sequence by atmospheric plasma spraying technology. The process parameters are shown in Table 2. The total coating thickness is 1.2 mm.

[0041] Table 2 Process parameters of plasma sprayed CoCrAlY and YSZ coatings

[0042]

[0043] (5) Finish the bushings and bearings according to the drawings;

[0044] (6) The silicone-based resin precursor is applied to the area of ​​the bushing that is not covered by the thermal spraying by brushing, and then placed in a heat treatment tank for 300°C × 2h, and cooled to room temperature in the furnace.

[0045] Comparative Example 1

[0046] After the cobalt-based alloy is cut into a specimen of a specified shape, the surface is ground and polished to a roughness of <Ra0.4μm。

[0047] Comparative Example 2

[0048] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0049] (2) Process the cobalt-based alloy into shaft sleeves and bearing shells according to the drawings.

[0050] Comparative Example 3

[0051] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0052] (2) Processing the cobalt-based alloy into a shaft sleeve according to the drawing;

[0053] (3) Process YSZ ceramic tiles according to drawings;

[0054] (4) Processing the cobalt-based alloy into a tile seat according to the drawing;

[0055] (5) Assemble the tile block in step (3) into the tile seat in step (4) at a specified temperature.

[0056] At room temperature, a φ6.35mm YSZ ceramic grinding ball was used to reciprocately rub the samples in Example 1 and Comparative Example 1 with a friction stroke of 5mm, a frequency of 10Hz, a load of 10N, and a time of 30min. At room temperature, a φ6.35mm Al2O3 ceramic grinding ball was used to reciprocately rub Example 1 with a friction stroke of 5mm, a frequency of 10Hz, a load of 10N, and a time of 30min.

[0057] After friction and wear, optical microscope, 3D profilometer and other equipment were used to compare and observe the wear marks of the worn grinding balls and samples. The results are shown in Figures 1 (a) to 3 (b).

[0058] The results of reciprocating friction of the grinding balls of Example 1 and Comparative Example 1 by YSZ are analyzed: According to the characterization results of Figures 1(a), 1(b), 2(a), and 2(b), the longest distance of the wear surface of the grinding balls of Example 1 after wear is 0.88 mm, and the longest distance of the wear surface of the grinding balls of Comparative Example 1 is 1.01 mm, and the surface of the grinding balls of Comparative Example 1 is adhered with cobalt-based alloy, indicating that relatively obvious adhesive wear occurs; according to Figure 4 , Figure 5 The characterization results show that the deepest depth of the wear scar in Example 1 is 10.2 μm, and the deepest depth of the wear scar in Comparative Example 1 is 26.4 μm, and the wear scar depth is 2.59 times that of Example 1, indicating that the degree of wear in Comparative Example 1 is significantly greater than that in Example 1; Figure 7 According to the characterization results, the wear volume, half-height width and wear scar depth of Example 1 are significantly smaller than those of Comparative Example 1. In summary, the wear resistance of the friction pair of Example 1 is much better than that of Comparative Example 1.

[0059] The results of reciprocating friction between the YSZ grinding balls and the Al2O3 grinding balls in Example 1 were analyzed: According to the characterization results in Figures 1(a), 1(b), 3(a), and 3(b), the longest wear distance of the YSZ grinding balls in Example 1 was 0.88 mm, and the longest wear distance of the Al2O3 grinding balls in Example 1 was 1.00 mm. In addition, there was a certain amount of Si-SiC adhered to the surface of the grinding balls, indicating that there was a certain amount of adhesive wear when grinding with Al2O3. Figure 4 , Figure 6 The characterization results show that the deepest depth of the wear scar between Example 1 and YSZ is 10.2 μm, and the deepest depth of the wear scar between Example 1 and Al2O3 is 18.2 μm, indicating that the wear degree of the same coating using different friction pairs is different, and the wear degree of YSZ grinding ball is significantly less than that of Al2O3 grinding ball; Figure 7According to the characterization results, the wear volume, half-height width and wear scar depth of the YSZ grinding ball in Example 1 are significantly smaller than those of the Al2O3 grinding ball. In summary, even if the same material is used, from the perspective of friction and wear results, it is necessary to select a suitable grinding material to obtain relatively good wear resistance, so the selection of friction pairs also requires creative work.

[0060] The shaft sleeves and bearings of Example 2 and Comparative Examples 2 and 3 were respectively installed in an AlSi experimental pot at a temperature of 650° C. to simulate the application of the shaft sleeves and bearings in an AlSi production line.

[0061] After 10 days of experiment, Example 2 ran relatively stably. After stopping the machine and taking out the bushings and bearings, they were cleaned and inspected. It was found that although the composite coating on the surface of the bushings and bearings was worn (wear amount <0.3mm, single side, the same below), the coating was still intact and had not failed, indicating that the service life of the bushings and bearings of Example 2 was >10 days. After 3 days of stable operation of Example 2, the sinking roller began to shake. After stopping the machine to take out the sleeve and bearing, the sleeve and bearing were cleaned and inspected, and it was found that the sleeve and bearing were severely worn. After measurement, the dimensions of the sleeve and bearing were reduced by 1.5~3mm at various locations. This was the fundamental cause of the shaking of the sinking roller; Example 3 only ran smoothly for about 3.5 days, and the sinking roller began to shake abnormally. After stopping the machine to take out the sleeve and bearing, the sleeve and bearing were cleaned and inspected, and it was found that the bearing was also broken. This was the fundamental cause of the abnormal shaking of the sinking roller. The sleeve wear of Example 3 was slightly better than that of Example 2, with a wear amount ranging from 1.0 to 1.2mm, but the surface condition of the sleeve was obviously worse than that of Example 2.

[0062] In summary, the shaft sleeve and bearing shell prepared by the method of the present invention are suitable for the aluminum silicon production line, which solves the problem of the non-wear resistance of the previous metal sleeve-metal shell system and the unstable service life of the metal sleeve-ceramic shell, and further improves the service life of the bearing shell and shaft sleeve, and the improvement effect is very obvious.

[0063] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A special sleeve bearing for aluminum silicon wire, characterized in that: The wearing parts on the bushing substrate are covered with a composite coating, and other parts are coated with a silicon-based resin. The substrate of the bushing is a cobalt-based heat-resistant alloy or 316L stainless steel. The composite coating material system of the bushing wearing parts is CoCrAlY / Y2O3-Si / SiC, and the coating thickness is 0.4~1.0mm. The composite coating material system of the bushing wearing parts is CoCrAlY-YSZ, and the coating thickness is 0.5~1.5mm.

2. A method for preparing a special sleeve and bearing for aluminum silicon wire as claimed in claim 1, characterized in that: The following steps are involved: S1, using supersonic flame spraying technology or laser cladding to deposit CoCrAlY / Y2O3 raw material powder and Si / SiC raw material powder on the sleeve to form a CoCrAlY / Y2O3-Si / SiC coating, and using supersonic flame spraying technology, atmospheric plasma spraying technology or laser cladding technology to deposit CoCrAlY-YSZ coating on the bearing shell; S2, depositing liquid silicon-based polymer precursor onto the position of the bushing and bearing not covered by the thermal spraying / laser cladding coating by brushing or liquid spraying, and curing it in a high temperature environment of 200~400℃ to obtain heat-resistant and corrosion-resistant silicon-based resin.

3. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the CoCrAlY / Y2O3 raw material powder is prepared from CoCrAlY and Y2O3 by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of CoCrAlY to Y2O3 is 5:1-50:

1.

4. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the Si / SiC raw material powder is prepared from Si and SiC by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of Si to SiC is 20:1-1:

20.

5. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the CoCrAlY / YSZ raw material powder is prepared by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation of CoCrAlY and YSZ, and the mass ratio of CoCrAlY to YSZ is 5:1-50:

1.

6. An application of the special sleeve and bearing for aluminum-silicon wire as claimed in claim 1 in a hot-dip AlSi coating production line.

7. An application of the special sleeve and bearing for aluminum silicon wire as claimed in claim 1 in a hot-dip galvanizing or zinc alloy production line.

Citation Information

Patent Citations

  • Axle sleeve and bush for zinc plating pot roller and its making method

    CN101117978A

  • Fiber-reinforced explosion-proof pipe composite coating for boiler pipe heated surface and preparation thereof

    CN111876716A

  • Aluminum-silicon roller bushing in continuous hot-dip aluminum-silicon plating unit and preparation method of aluminum-silicon roller bushing

    CN116265598A

  • High-temperature-resistant, self-lubricating and low-friction sealing coating material and preparation method thereof

    CN116770214A

  • Continuous hot dip metal coating apparatus, and roll and bearing therefor

    JP2001335905A

Cited By

  • Method for improving sintering speed and uniformity of composite shaft sleeve copper powder

    CN121315283A